The retreat of the interventionist state in advanced democracies - Zohlnhöfer, Reimut; Engler, Fabian; Dümig, Kathrin (British journal of political science, 2018)
Why have advanced democracies experienced a retreat of the interventionist state since 1980? This article provides evidence that in all relevant policy indicators (spending, subsidies, state-owned enterprises, regulation, capital taxation) government intervention has been scaled back across the OECD. An overview of the results of 130 quantitative studies analysing at least one of these indicators is provided. Focusing on five main explanatory variables - globalization, Europeanization, learning and emulation, socio-economic problems, and political parties - only limited agreement in the literature is found. The reasons for this disagreement are discussed. Ways forward are suggested for the theoretical models on which studies are based, how the dependent variable is chosen, the empirical approaches that may be applied, and how quantitative research and comparative case studies may be combined.